Implementation of the Adiwiyata School Program in Building Environmental Care Character at Elementary School - Kabul Trikuncahyo; Imam Sujono; Dian Septi Nur Afifah; Rahyu Setiani (Salus Publica: Journal of Community Service, 2026)
This study aims to describe the implementation of the Adiwiyata School Program in building environmental care character at SD Negeri 1 Ngrandu, Trenggalek. The Adiwiyata Program, jointly initiated by the Ministry of Environment and Forestry and the Ministry of Education and Culture, seeks to create schools as learning centers that cultivate environmental responsibility. This research employed a qualitative approach with a case study design. Research subjects included the school principal, Adiwiyata team, seven teachers, school committee, and twelve students from grades 4, 5, and 6. Data were collected through participatory observation, in-depth interviews, and documentation studies, then analyzed using Miles and Huberman's interactive model encompassing data condensation, data display, and conclusion drawing. Data validity was verified through source triangulation and technique triangulation. The findings reveal that: (1) planning was conducted in a participatory and systematic manner through the Environmental Potential and Problem Identification (IPMLH) process involving all stakeholders; (2) implementation covered all four main components—environmental policy, environment-based curriculum, participatory environmental activities, and eco-friendly facility management; (3) changes in students' environmental character progressed across the knowing, feeling, and acting domains; (4) integration of Islamic spiritual values such as the concepts of khalifah fil ardh and amanah strengthened intrinsic motivation and behavioral consistency; and (5) key supporting factors included exemplary leadership and teacher commitment, while inhibiting factors encompassed budget constraints, high teacher workload, and inconsistency between school and home habits.